ANALYSIS OF THE EXPRESSION OF POTATO URIDINEDIPHOSPHATE-GLUCOSE PYROPHOSPHORYLASE AND ITS INHIBITION BY ANTISENSE RNA - Sonnewald, Uwe; et al. (Planta, 1993)
The expression of the enzyme UDP-glucose pyrophosphorylase (UGPase; EC 2.7.7.9) from potato (Solanum tuberosum L.) was analysed with respect to sink-source interactions and potato tuber storage. The highest level of expression was found in developing tubers, the strongest sink tissue. Storage of mature tubers at low temperatures led to an increase of the steady-state level of UGPase mRNA, implicating a role of this enzyme in the process of ''cold-sweetening''. Transgenic plants were created expressing UGPase antisensee RNA under the control of the 35S promoter of the Cauliflower Mosaic Virus with the polyadenylation signal of the octopine-synthase gene. Regenerated plants were tested for reduction of UGPase at the RNA, protein and activity levels. Plants with a 95%-96% reduction of UGPase activity in growing tubers showed no change in growth and development. Also, carbohydrate metabolism in tubers of these plants was not substantially affected, indicating that only 4% of the wild-type UGPase activity is sufficient for the enzyme to function in plant growth and development.
Keywords: ANTISENSE RNA; CARBOHYDRATE METABOLISM; ENZYME EXPRESSION ANALYSIS; SOLANUM; TRANSGENIC POTATO; URIDINEDIPHOSPHATE GLUCOSE PYROPHOSPHORYLASE